The Relationship Between Nutritional Knowledge in Mothers and Recommended Infant Feeding Practices in Children 0–24 Months in the Lubombo region of eSwatini. (29th May 2020) - Dallmeier, Alina; Gewa, Constance
Abstract: Objectives: The purpose of this study was to determine if nutritional knowledge is associated with recommended infant feeding practices among mothers in the Lubombo region of eSwatini. Methods: In April 2019, we conducted a cross-sectional survey to assess knowledge and practices among mothers (18–49 years) with at least one young child (0–24 months) in the Siphofaneni Tinkhundla (Administrative subdivision) of the Lubombo region of eSwatini. Community health workers invited mothers to a central meeting location were quantitative data was collected through one-on-one interviews. The questionnaire was broken up into four sections: 1) Sociodemographic, 2) Household Food Security Assessment, 3) Nutrition Practices, and 4) Nutrition Knowledge. Mothers were 18–48 years of age (mean: 26.95; SD: 6.5). We used logistic and multivariate regression to measure the association between breastfeeding practices and nutrition knowledge, and the association between diet diversity and nutrition knowledge. Results: A total of 164 mothers completed the questionnaire. Participants were 18–48 years of age (mean: 26.95; SD: 6.5). Their children were 0–24 months of age (mean: 10.4; SD: 6.3). The total nutrition knowledge score ranged from 8 to 44 (mean: 21.8; SD: 6.14). Approximately 92% had heard of exclusive breastfeeding; of those mothers, 87% were able to properly explain the practice. Ninety three % of infants 0–5 months were breastfed, but less than half of those were exclusively breastfed. Exclusive breastfeeding practices were not significantly associated with nutrition knowledge. The mean for the Minimum Diet Diversity score was 3.7 (SD 1.38). Diet Diversity scores and nutrition knowledge were significantly associated ( P  = .011) after adjusting for infant sex, maternal education and household size. Conclusions: Education alone may not be sufficient for the adoption of recommended infant feeding practices among mothers. Future research should explore sociocultural and economic factors that may play a role in influencing recommended infant feeding practices. Funding Sources: This study was funded by the Fulbright U.S. Student Program.